2018
DOI: 10.1186/s11658-018-0107-z
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Inhibition of inflammation using diacerein markedly improved renal function in endotoxemic acute kidney injured mice

Abstract: BackgroundInflammation is an important pathogenic component of endotoxemia-induced acute kidney injury (AKI), finally resulting in renal failure. Diacerein is an interleukin-1β (IL-1β) inhibitor used for osteoarthritis treatment by exerting anti-inflammatory effects. This study aims to investigate the effects of diacerein on endotoxemia-induced AKI.MethodsMale C57BL/6 mice were intraperitoneally injected with lipopolysaccharide (LPS, 10 mg/kg) for 24 h prior to diacerein treatment (15 mg/kg/day) for another 48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Mass spectrometry analysis of the same renal samples revealed that the concentration of apuaporin-1 (Aqp1), an already validated target of miR-144-3p [28] decreased at 24 h when miR-144-3p was upregulated, suggesting a possible regulation of Aqp1 by miR-144-3p. LPS downregulated both mRNA and protein expression of Aqp1 in mouse kidneys [29,30]. Just as in our study, Aqp1 protein was first elevated and later decreased in the kidney [30].…”
Section: Discussionsupporting
confidence: 84%
“…Mass spectrometry analysis of the same renal samples revealed that the concentration of apuaporin-1 (Aqp1), an already validated target of miR-144-3p [28] decreased at 24 h when miR-144-3p was upregulated, suggesting a possible regulation of Aqp1 by miR-144-3p. LPS downregulated both mRNA and protein expression of Aqp1 in mouse kidneys [29,30]. Just as in our study, Aqp1 protein was first elevated and later decreased in the kidney [30].…”
Section: Discussionsupporting
confidence: 84%
“…A large body of preclinical work has investigated several pathways to potentially intervene and prevent or treat SA-AKI, and although this work has focused on molecules such as the caspase and interleukin inhibitors, to date it has not translated into human investigations of SA-AKI 162163164165Table 5. summarizes several clinical trials that have investigated novel and traditional agents in the setting of SA-AKI.…”
Section: Prevention and Medical Treatmentmentioning
confidence: 99%
“…WT1 plays an important role in the genitourinary development and maintenance of podocytes throughout life (9). WT1 mutations are associated with a broad spectrum of clinical phenotypes (11,26,27), immunosuppressive treatment and renal alterations indicate that immunity and inflammation play an important role in the pathogenesis of diabetic kidney disease (28) and nephrotic syndrome (29). The steroid-resistant nephrotic syndrome is due to the loss of WT1 function during the development and maintenance of podocytes (7,11) and corticosteroids are the mainstay of treatment (29) and have reduced the death rate to around 3% (30).…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that immunity and low-grade inflammation are an important component of the pathogenesis of diabetic kidney disease. Inflammation has become a center of interest in kidney injury, along with increased levels of inflammatory cytokines, such as IL1β, TNFα and monocyte chemoattractant protein-1 both in patients and in experimental models (28). The objective of this study was to analyze how the inflammatory process modulates the expression and posttranslational activity of WT1 and how it affects its functionality as a transcription factor in podocytes in mice treated with LPS.…”
Section: Discussionmentioning
confidence: 99%